Production of microbial transglutaminase on media made from sugar Cane molasses and glycerol - Portilla-Rivera, Oscar M. (Array, 2009)
Summary: Transglutaminase is an enzyme that catalyses an acyl transfer reaction between γ-carboxamide groups of glutaminyl residues and lysine residues in proteins. Due to this property, this enzyme is used for enhancing textural properties of protein-rich food. The transglutaminase used as food additive is obtained by microorganisms, mainly by Streptoverticillium ladakanum. On the other hand, sugar cane molasses is a viscous liquid rich in noncrystallized carbohydrates (saccharose, glucose and fructose). In this work, the feasibility of using sugar cane molasses as a carbon source for the production of microbial transglutaminase by Streptoverticillium ladakanum NRRL 3191 has been studied. Carbon sources including sugar cane molasses (60 g of total sugars per L), glycerol (60 g/L) and their mixture in a ratio of 1:1 (30 g/L of each) were evaluated. Time course of microbial growth, transglutaminase activity and carbon source consumption were determined every 24 h during 120 h of fermentations at three agitation speeds (200, 300 or 400 rpm). The results showed that with the increase in agitation speed, the biomass concentration increased up to 8.39 g/L in the medium containing sugar cane molasses alone or the mixture of molasses and glycerol. The highest transglutaminase activity was obtained at 400 rpm in the medium containing a mixture of molasses and glycerol, reaching 0.460 U/mL, while in the medium containing sugar cane molasses alone, the activity was 0.240 U/mL, and using glycerol alone it was 0.250 U/mL. These results show that sugar cane molasses is a suitable medium for transglutaminase production when it is combined with glycerol